Governance Failure in Village-Owned Enterprises: Formal–Informal Institutional Dynamics and Village Business Performance - Muh Tang Abdullah; Ralaivao Hanginiaina Emynorane; Much Faisal Syaputra; Rizal Pauzi (Universitas Teuku Umar, 2026)
This study aims to analyze how interactions between formal and informal institutions generate governance failure in the management of Village-Owned Enterprises (BUM Desa) and explain variations in village business performance. Employing a qualitative multiple-case study design, the research was conducted in five villages in Mamuju Tengah Regency, Indonesia. Data were collected through in-depth interviews, document analysis, non-participant observation, and process tracing, and analyzed using thematic coding, process tracing, and cross-case comparison. The findings show that although formal governance instruments such as village regulations, bylaws, standard operating procedures, and accountability mechanisms are formally established, they are systematically undermined by dominant informal institutions, including patronage networks, kinship relations, elite control, and norms discouraging criticism. This institutional misalignment distorts decision-making, weakens accountability, and limits transparency, resulting in poor business planning and stagnation of BUM Desa business units. Cross-case analysis further reveals that governance outcomes are contingent rather than uniform, mediated by leadership style, administrative capacity, legal readiness, and social capital, which shape the balance between formal and informal institutions. The study concludes that governance failure in BUM Desa is driven less by technical or managerial deficiencies than by the dominance of informal institutions over weakly enforced formal rules. These findings underscore the importance of institutional reforms that address informal power relations and leadership accountability to strengthen village economic governance.